(untitled) - Marshall, Edward M. (New York, 1995)
This guide examines how to replace the outdated, inefficient albatross of hierarchy with a new "culture of collaboration." It shows how to understand and apply a revolutionary process for changing the way we manage our companies and foster true teamwork. The author shows how managers can create "operating agreements" and become collaborative leaders using self-assessment action plans.
Keywords: Work ethic,Cooperativeness,Management